2012
DOI: 10.1056/nejmoa1205512
|View full text |Cite
|
Sign up to set email alerts
|

Prasugrel versus Clopidogrel for Acute Coronary Syndromes without Revascularization

Abstract: Among patients with unstable angina or myocardial infarction without ST-segment elevation, prasugrel did not significantly reduce the frequency of the primary end point, as compared with clopidogrel, and similar risks of bleeding were observed. (Funded by Eli Lilly and Daiichi Sankyo; TRILOGY ACS ClinicalTrials.gov number, NCT00699998.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
404
1
19

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 780 publications
(439 citation statements)
references
References 15 publications
11
404
1
19
Order By: Relevance
“…end point of cardiovascular death, MI, and stroke was reported between treatment with prasugrel or clopidogrel. 27 None of the safety end points was s ignificantly different between the two study groups.…”
Section: Prasugrelmentioning
confidence: 89%
See 1 more Smart Citation
“…end point of cardiovascular death, MI, and stroke was reported between treatment with prasugrel or clopidogrel. 27 None of the safety end points was s ignificantly different between the two study groups.…”
Section: Prasugrelmentioning
confidence: 89%
“…26 The second major phase III study in which prasugrel was compared with clopidogrel was the TRILOGY ACS trial. 27 This trial included a population of 9,326 patients with ACS who were being medically managed. The daily dose of prasugrel was reduced to 5 mg (instead of 10 mg) for patients aged ≥75 years and those with a body mass <60 kg.…”
Section: Prasugrelmentioning
confidence: 99%
“…In the TRILOGY ACS (Targeted Platelet Inhibition to Clarify the Optimal Strategy to Medically Manage Acute Coronary Syndromes) trial [25], prasugrel showed no benefits over clopidogrel in reducing death from cardiovascular causes, myocardial infarction or stroke among patients with ACS who were not undergoing PCI.…”
Section: Phase III Studies: Triton Timi 38 and Platomentioning
confidence: 99%
“…Given the prevalence of ischaemic heart disease, previous studies have largely examined prognostic risk factors for the development of HF subsequent to acute coronary syndrome (ACS) 3, 4. To that effect, surgical revascularization in the form of coronary artery bypass grafting (CABG) surgery remains an important treatment modality for patients suffering from ACS 5.…”
Section: Introductionmentioning
confidence: 99%